2014
DOI: 10.5539/ijef.v6n9p165
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark for REIT Performance in Malaysia Using Hedonic Regression Model

Abstract: This paper focuses on the setting of a benchmark for the REIT performance within the REIT industry to achieve a sector induced national REIT index for Malaysia. The study has as objectives to (i) explore literatures on performance and benchmarking; (2) appraise REIT performance analysis as presented in the past studies; and (3) propose Hedonic Regression Model analysis towards setting a benchmark for REIT. The study adopted the quantitative research and analysis method. Three conventional REITs were purposivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The study concluded that investing in M-REITs will provide a preferable return because every one of the M-REITs outperformed the market benchmark during the time period. This is further reinforced in a study by Olanrele et al (2014), who analysed the performance of three M-REITs over a five-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014) using a hedonic regression model. The study found that all the M-REITs outperformed the market index throughout the time period, albeit with some sectoral capacity underperformance.…”
Section: Overviewmentioning
confidence: 93%
“…The study concluded that investing in M-REITs will provide a preferable return because every one of the M-REITs outperformed the market benchmark during the time period. This is further reinforced in a study by Olanrele et al (2014), who analysed the performance of three M-REITs over a five-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014) using a hedonic regression model. The study found that all the M-REITs outperformed the market index throughout the time period, albeit with some sectoral capacity underperformance.…”
Section: Overviewmentioning
confidence: 93%
“…Firm size has been measured commonly by total market capitalisation (natural logarithm of market capitalisation) and total assets (Kim, 2001). Prior research showed mixed results for the relationship between firm size and return performance (Ambrose & Linneman, 2001;Chang et al, 2015;Mclntosh et al, 1991;Olanrele et al, 2014). According to Ambrose (2001), larger firms should increase the rate of return due to a higher profit margin and lower cost of capital.…”
Section: Market Capitalisationmentioning
confidence: 99%
“…This finding was supported by Das and Bhattacharya (2013), which concluded that ROE had a significant relationship with stock return. The possible explanation for the negative relationship was due to the simultaneous effects of all financial determinants on the annual return and no variable should be considered individually and isolated from others to reflect the true association between ROE and annual return as suggested by Olanrele et al (2014). Another possible explanation concerning the negative relationship may be due to the declining trend in ROE due to increases in accumulated retained profit while the net income from the property was relatively stable.…”
Section: Regression Analysis and Regression Coefficientsmentioning
confidence: 99%
“…Hedonic analysis is originally the study of the relationship between the price of a product and the characteristics of the product. It was first applied in 1926 to value the price of farmland (Olanrele et al 2014). The hedonic pricing model has been widely discussed academically and accepted as a way of assessing the price of real estate which has a variety of attributes.…”
Section: Assumptions About Growth Environment Commentsmentioning
confidence: 99%